Methods to determine the mine gas explosibility - An overview - Cheng, Jianwei; Wang, C.; Zhang, S. (2012)
Mine gas explosions present a serious safety threat in the worldwide mining industry. Since the beginning of mining, many coal miners have been killed due to the explosions. Accordingly, on a regular basis, mine operators should get air samples from the underground atmosphere. At the same time, monitoring and tracking the explosibility of the air sample should be done as a timely matter to avoid any potential explosions. All these works can provide very important information to assist the mine operators to well understand the mine atmospheric status and its trends. In additional, when facing the coal spontaneous combustion, mine fire events, or other chemical reactions related mine accidents, determination of explosibility is a definitely significant work for the safety of miners and mine rescue personnel especially when planning and implementing any mine rescue strategies. For many years, mining engineers and researchers have developed a number of methods for assessing the explosibility of the air-gas-mixture. Their research results provide a baseline for judgments of the mine gas explosibility and in determining the extent of change. In this paper, main popular and typical methods used in mining industry to determine the mine gas explosibility are introduced and reviewed. Case demonstrations for each method are also shown and can be used to instruct readers to understand how to apply them. Finally, a brief discussion about the current methods is presented and some preliminary suggestions are also listed for the further improvements in the future research. © 2011 Elsevier Ltd.